It is time to combine the two main traditions in the research on the neural correlates of consciousness: C = L × D - Bachmann, Talis; Hudetz, Anthony G. (Frontiers in Psychology, 2014)
Research on neural correlates of consciousness has been conducted and carried out mostly from within two relatively autonomous paradigmatic traditions – studying the specific contents of conscious experience and their brain-process correlates and studying the level of consciousness. In the present paper we offer a theoretical integration suggesting that an emphasis has to be put on understanding the mechanisms of consciousness (and not a mere correlates) and in doing this, the two paradigmatic traditions must be combined. We argue that consciousness emerges as a result of interaction of brain mechanisms specialized for representing the specific contents of perception/cognition – the data -- and mechanisms specialized for regulating the level of activity of whatever data the content-carrying specific mechanisms happen to represent. Each of these mechanisms are necessary because without the contents there is no conscious experience and without the required level of activity the processed contents remain unconscious. Together the two mechanisms, when activated up to a necessary degree each, provide conditions sufficient for conscious experience to emerge. This proposal is related to pertinent experimental evidence.